Factors Influencing Recanalization After Mechanical Thrombectomy With First-Pass Effect for Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Bai, Xuesong; Zhang, Xiao; Wang, Jie; Zhang, Yinhang; Dmytriw, Adam A.; Wang, Tao; Xu, Ran; Ma, Yan; Li, Long; Feng, Yao; Mena, Carolina Severiche; Yang, Kun; et al. (Frontiers in Neurology, 2021)
Background: First pass effect (FPE) is increasingly recognized as a predictor of good outcome in large vessel occlusion (LVO). This systematic review and meta-analysis aimed to elucidate the factors influencing recanalization after mechanical thrombectomy (MT) with FPE in treating acute ischemic stroke (AIS). Methods: Main databases were searched for relevant randomized controlled trials (RCTs) and observational studies reporting influencing factors of MT with FPE in AIS. Recanalization was assessed by the modified Thrombolysis in Cerebral Ischemia (mTICI) score. Both successful (mTICI 2b-3) and complete recanalization (mTICI 2c-3) were observed. Risk of bias was assessed through different scales according to study design. I2 statistic was used to evaluate the heterogeneity, while subgroup, meta-regression and sensitivity analysis were performed to investigate the source of heterogeneity. Visual measurement of funnel plots was used to evaluate publication bias. Results: A total of 17 studies and 6186 patients were included. Among them, 2068 patient achieved recanalization with FPE. The results of meta-analyses showed that age (mean deviation (MD):1.21,95% confidence interval (CI): 0.26-2.16; p=0.012), female gender (odds ratio (OR):1.12,95% CI: 1.00-1.26; p=0.046), diabetes mellitus (DM) (OR:1.17,95% CI: 1.01-1.35; p=0.032), occlusion of internal carotid artery (ICA) (OR:0.71,95% CI: 0.52-0.97; P=0.033), occlusion of M2 segment of middle cerebral artery (OR:1.36,95% CI: 1.05-1.77; p=0.019), duration of intervention (MD:-27.85, 95%CI: -42.11--13.58; p<0.001), time of onset to recanalization (MD:-34.63, 95%CI: -58.45--10.81; p=0.004), general anesthesia (OR:0.63,95% CI: 0.52-0.77; p<0.001) and use of balloon guide catheter (BGC) (OR:1.60,95% CI: 1.17-2.18; p=0.003) were significantly associated with successful recanalization with FPE. At the same time, age, female gender, duration of intervention, general anesthesia, use of BGC, and occlusion of ICA were associated with complete reperfusion with FPE, but M2 occlusion and DM were not. Conclusion: Age, gender, occlusion site, anesthesia type and use of BGC were influencing factors for both successful and complete recanalization after first pass thrombectomy. Further studies with more comprehensive observations indexes are need in the future.